ENSINO HÍBRIDO: UMA ANÁLISE BIBLIOGRÁFICA DAS PUBLICAÇÕES NO PORTAL DE PERIÓDICOS - CAPES - MUCHUELO, NEI (2019)
Blended Learning is neither a new term nor a revolutionary concept for the classroom. However, the way it is interpreted can be hopeful or harmful depending on how it is implemented. Blended Learning has held a place in educational change discourses for more than a decade, but it cannot be a movement that shifts the human dimension of learning with an economic imperative to reduce labor costs by halving the teaching population, cutting certified teachers in favor of massive online groups of students instructed by "facilitators" or "individual learning experts. Technologies should be employed to help students become empowered citizens, rather than passive consumers. Innovations in education are needed to help create a society where people can flourish in culturally rich, informed, democratic, digitally connected and diverse communities; we must achieve a more subtle balance that combines digital technologies and the physical presence of a caring, knowledgeable and pedagogically thoughtful teacher. This is not an optional "good to have," but a "must have. The methodology of this work comprises in a bibliographic research, called state of knowledge, it is the survey of the bibliography already published with the purpose of putting the researcher in direct contact with everything that was written about a certain subject. This research takes a qualitative approach, with documentary exploration of material, although it presents some quantitative data to express the overview of the articles identified. The objective is to describe by means of the bibliographic research of scientific production on the publications of hybrid education, performing a systematic review for the period from 2005 to 2018, for the research, 40 articles were selected, 21 in the field of Administration and 19 in the field of Education, based on the CAPES Gate of Scientific Journals, CAPES was chosen to be consulted, due to its importance and sophistication in academy. Data collection occurs through consultation on the websites of the portal, through the keywords "hybrid teaching", and the following script of procedures was used for the analysis of qualitative data, reading with attention to the texts; analysis and highlighting of text elements; search for patterns in the analyzed texts (similarities) and grouping of keywords. The results found were that this trend deconstructs the fixed concepts that differentiate face-to-face classes from virtual ones, because it unifies the perception of education and learning, regardless of the medium that will be transmitted. It is a fact that a good class and qualified teachers in teaching will never replace devices, technologies or systems. But making education more attractive and integrated with students' habits through hybrid teaching not only facilitates the work of the educators involved but also makes students more informed and interested in the entire learning process.